Acute coronary events in SARS-CoV-2 - causal or incidental? - Shatabhisha Mandal; Gajender Singh Ranga; Narang, Shiva; Tandon, Anupama (Asian Journal of Medical Sciences, 2023)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus can damage respiratory, cardiovascular system by various mechanism which can lead to increased morbidity and mortality. Aims and Objectives: The aim of the study was to assess incidence of acute coronary syndrome (ACS) in moderate to severe cases of infection with SARS-CoV-2. Materials and Methods: This was an observational cross-sectional study including 60 patients of age ≥18 years of either gender presenting to GTB Hospital diagnosed as positive for SARS-CoV-2 by RT-PCR and/or Rapid Antigen Test and belonging to moderate and severe category without any prior history of respiratory, cardiac, gastrointestinal, renal illness, long-term corticosteroid, or immunomodulator use. The cardiac involvement was assessed by history, clinical examinations, and investigations. Results: Cardiovascular involvement was present in 25% patients. Cardiac involvement included ACS including ST elevation myocardial infarction (STEMI) (3.3%), non-STEMI (10%), unstable angina (1.67%), left ventricular hypertrophy (8.3%), bundle branch block (3.3%), atrial fibrillation (1.67%), and bradycardia (1.67%). Raised cardiac enzyme levels positively correlated with ECG abnormalities. Respiratory involvement was seen in 85% of patients. among which 56.7% patients in severe category, 41.67% patients in moderate category, and 1.67% patients in mild category as per CTSI scoring. There was lung parenchymal involvement with ground glass opacities in bilateral lungs (68.3%), lobar consolidation (6.7%), cavitatory lesion (5%), pulmonary edema (5%), pneumothorax (3.3%), emphysematous changes (3.3%), and bilateral pleural effusion (3.3%). Conclusion: ACS occurs frequently in patients with SARS-CoV-2 and it is associated with complications such as congestive heart failure, bundle branch block, atrial fibrillation, bradycardia, and heart block.